Fault Type Classification in the Presence of Inverter-Based Resources: Review, Challenges, and Future Works - Mohammad Mehdi Mobashsher; Seyyed Mehdi Hosseini; Ali Akbar Abdoos; Sayyed Mohammad Hashemi; Majid Sanaye-Pasand; Maher Azzouz (IEEE Access)
Fault type classification (FTC) is a major unit of industrial distance relays that affects some other protective schemes such as single-pole tripping and reclosing, fault location and etc. Traditional FTC techniques make use of either phase changes between current symmetrical components or magnitude differences between superimposed currents. Since inverter-based resources (IBRs) have different current signatures than those of synchronous generators, conventional FTC approaches suffer from misrecognition when applied to a transmission line emanating from an IBR. The fault current contribution of IBRs is determined by the host grid code (GC) and the internal controller. Therefore, this paper demonstrates the limitations of the conventional FTC methods employed in industrial applications for protection of lines that originate from IBRs under modern host GCs. First, the influence of various GCs on the classic FTC techniques is analyzed based on the negative-sequence control strategies. Then, some experimental tests are executed to evaluate the accuracy of industrial FTC methods in the attendance of IBRs. After that, various newly proposed FTC methods in the presence of IBRs are studied, and their advantages and disadvantages are discussed. Lastly, potential research gaps in the area of FTC with IBRs are noted for further study and investigation in academic circles.